The Guideline of Creating Learning City for Elderly in Line with UNESCO - Chuengsamran, Kornkamol; Keawkongthong, Sirikarn; Punjasutaros, Chalermporn (Journal of Dhamma for Life, 2025)
This article aims to explore guideline for creating a learning city for elderly based on the development and creation of UNESCO's learning cities. The study examined relevant documents about establishing learning cities in cities that are part of the UNESCO Global Network of Learning Cities (GNLC). It also highlights the key initiatives that promote learning for elderly domestically and internationally, including the cities of Shanghai (People's Republic of China), Suwon (Republic of Korea), and in Thailand, Chiang Rai and Phayao. The synthesis of the information was categorized according to the guidelines for developing and creating a learning city by UNESCO, which include: 1) Develop a plan, 2) Involve all stakeholders, 3) Celebrate learning, 4) Make learning accessible to all, 5) Monitor and evaluate progress, and 6) Ensure sustainable funding. The study showed that each city has its own unique approach in establishing Learning Cities (LC), but there are common elements. These include setting a clear vision, goals, and mechanisms for driving LC that promotes collaboration between the government, all stakeholders, and the local community. Additionally, the establishing of committee which consists of stakeholders from various sectors is crucial. Furthermore, learning resources and learning spaces are created spread throughout the city, ensuring that they are within walking distance for the elderly. It is also found that there is a regular survey of the needs and satisfaction of learners in order to develop and improve the courses for the elderly, based on their needs and interests.